1994
DOI: 10.1159/000178841
|View full text |Cite
|
Sign up to set email alerts
|

Fast Wavelength Scanning Reflectance Spectrophotometer for Noninvasive Determination of Hemoglobin Oxygenation in Human Skin

Abstract: Oxygen saturation of hemoglobin (HbSO2) in skin vessels may be determined with photometric methods. However, the optical complexity of the skin makes quantitative measurements difficult. A possible approach is the analysis of reflectance spectra using the two-flux theory of Kubelka and Munk. The final equation of this theory which describes the transformation between absorbed and reflected light has been approximated by a hyperbola. Based on this approximation we evaluated skin spectra obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 27 publications
5
20
0
1
Order By: Relevance
“…These S mb O 2 values are similar to other ORS studies of normal healthy human skin, which identified that the saturation of hemoglobin in dermal vessels was greater in acral skin of the extremities compared with proximal sites. For example, Caspary and colleagues reported mean(SD) oxygen saturation of 65(11.9)% for volar forearm and 90(3.9)% for tip of index finger (4), whereas others report mean oxygen saturations of 72.9(12.2)% for lateral forearm (33). All studies were performed with a skin temperature of 26 -31°C, although unfortunately the researchers did not specify the source-detector spacings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These S mb O 2 values are similar to other ORS studies of normal healthy human skin, which identified that the saturation of hemoglobin in dermal vessels was greater in acral skin of the extremities compared with proximal sites. For example, Caspary and colleagues reported mean(SD) oxygen saturation of 65(11.9)% for volar forearm and 90(3.9)% for tip of index finger (4), whereas others report mean oxygen saturations of 72.9(12.2)% for lateral forearm (33). All studies were performed with a skin temperature of 26 -31°C, although unfortunately the researchers did not specify the source-detector spacings.…”
Section: Discussionmentioning
confidence: 99%
“…Spectra ranging from 470 to 1,120 nm are acquired in 0.05 s, processed by use of a custom-written Windows-based software package, and analyzed by using MatLab (The MathWorks, Natick, MA). The protocol was designed to replicate the experimental technique suggested by Merschbrock and colleagues (33) in which reflectance spectra are obtained specifically from the blood volume in the skin and not the surrounding interstitium. Initially a reference spectrum is taken with pressure applied to the probe sufficient to occlude the superficial blood vessels.…”
Section: Orsmentioning
confidence: 99%
See 1 more Smart Citation
“…To minimize the effect of other absorbers in the tissue, a reference spectrum was initially taken by applying pressure to the probe sufficiently to occlude the superficial blood vessels. Subtracting this reference spectrum from the subsequent recorded blood-filled spectra produced a spectrum that could be attributed to absorption and scattering by blood alone and not the surrounding interstitium [21,22]. Due to the heterogeneity of the microvasculature and photosensitizer localization the oxygen saturation measurement was taken at the same point within the lesion on each occasion.…”
Section: Measuring Oxygen Saturationmentioning
confidence: 99%
“…Occlusion experiments were chosen as the behavior of blood volume and blood oxygenation over time is well known, which is ischemia during, and reactive hyperemia after occlusion. 4,8,29,30 All volunteers signed a consent form approved by the Institutional Review Board of the Eunice Kennedy Shriver National Institute of Child Health and Human Development under the Protocol No. 08-CH-0001.…”
Section: Occlusion Experiments On Healthy Volunteersmentioning
confidence: 99%